Constitutive polysaccharide degradation and diet-dependent lipid metabolism reveal an adaptive feeding strategy in the pacific oyster Magallana gigas - Manabu W.L. Tanimura; Kazuhiko Koike; Kazumi Matsuoka (PLoS ONE, 2026)
Previous studies have identified several endogenous cellulases in the Pacific oyster Magallana gigas , indicating its potential to assimilate terrestrial carbon sources. However, the mere presence of endogenous cellulases suggests capability but does not confirm actual feeding behavior. Here, we analyzed the transcriptomes of two groups of M. gigas fed with either cultured diatoms or terrestrial leaves. The results showed that although one GHF9 endoglucanase were upregulated in response to leaf feeding, other cellulase GH families exhibited no significant differences compared to the diatom-fed group. Moreover, xylanase expression levels remained unchanged, suggesting that enzymes involved in the decomposition of terrestrial carbohydrates may be maintained at a stable baseline. In contrast, enzymes related to fatty acid assimilation, specifically β-oxidation enzymes, were upregulated when oysters were fed diatoms. These findings suggest that M. gigas maintains a constitutive level of glycoside hydrolase expression to assimilate the “ubiquitous” terrestrial carbon source, while it upregulates related enzymes in response to the “occasional” availability of fatty acids from phytoplankton.